The politics of profit in Swedish welfare services: Four decades of Social Democratic ambivalence. (August 2019) - Meagher, Gabrielle; Szebehely, Marta
The Social Democratic architects of the Swedish welfare state considered public provision as well as public funding of welfare services essential to realising their egalitarian ambitions. However, since the early 1990s, a highly concentrated, for-profit sector has emerged in welfare service provision. We analyse how the Swedish Social Democrats have discussed privatisation and the profit motive in welfare services from the 1980s to the present. We find that Social Democratic governments have defended public provision weakly across the period. The driving factors include the eclipse of the egalitarian ideal in favour of ideals of choice and diversity, internal disunity within the party on the profit question, and change in the political power order in Sweden, such that private welfare companies and their interest organisations have gained and now wield significant influence over welfare service policy.